Advance Mineral Practices Techniques - Neha Sahu; Rizwan Arif (International Journal of Minerals, 2024)
In recent years, the field of mineral processing has witnessed significant advancements aimed at improving the efficiency, sustainability, and economic viability of mineral extraction and processing techniques. These advancements encompass a broad spectrum of practices, from ore sorting and comminution to flotation and tailings management. This paper reviews the latest innovations in mineral processing, focusing on key areas such as: Ore Sorting and Pre-Concentration: Implementation of sensor-based sorting technologies that enhance the grade and recovery of ore by detecting and separating valuable minerals from waste rock early in the process. Advanced Comminution Techniques: The creation of energy-saving grinding technologies, such as vertical roller mills and high-pressure grinding rolls (HPGR), which lower energy consumption and enhance particle size distribution. Hydrometallurgical Advances: Improvements in leaching and solvent extraction techniques that allow for more efficient recovery of metals from low-grade and refractory ores, reducing environmental impact. Tailings Management and Water Reclamation: Adoption of sustainable practices for tailings disposal, such as thickened and paste tailings, as well as advanced water treatment technologies that enable the reuse of process water and minimize freshwater consumption. The paper highlights case studies demonstrating the successful implementation of these advanced techniques in various mining operations worldwide. Together with the social and environmental ramifications, the possible economic advantages are also covered. These advancements represent a transformative shift towards more sustainable and efficient mineral processing practices, aligning with global efforts to meet the increasing demand for minerals while minimizing the ecological footprint of mining activities.
Keywords: Mineral processing; comminution; hydrometallurgy; ore sorting; tailings management